Integrating Peer Counselor Training in Psychological First Aid (PFA) to Reinforce University Counseling and Disability Support Systems - Silalahi, Ronald Maraden Parlindungan; Farisandy, Ellyana Dwi; Karuni, Bunga; Mutma, Fasya Syifa; Setiawan, Agustinus Agus (Sebatik, 2025)
Psychological First Aid (PFA) is an essential competency for peer counselors to support mental health among university students. To strengthen students’ knowledge and readiness in providing early psychological support, a one-day Peer Counselor Training was conducted involving 22 psychology students (mean age = 20.73 years). The training consisted of lectures, video, case discussions, demonstrations, supervised roleplay, reflection, and assessments covering mental health concepts, psychological disorders, non-suicidal self-injury, suicidal ideation, suicide attempts, suicide, dynamics of interpersonal relationships, and the core principles of PFA. Pre- and post-training assessments showed a clear improvement in participants’ knowledge. Due to the non-normal distribution of the posttest scores, a Wilcoxon Signed-Rank Test was performed, yielding statistically significant results (Z = -4.12, p < 0.001). This finding indicates that the training effectively enhanced students’ understanding of PFA. Participants also expressed high satisfaction with the learning materials, simulations, and media used, suggesting that the training methods were engaging and useful for practical skill development. They recommended longer simulation sessions and more interactive case-based discussions for future training. Importantly, the training strengthens the role of students as active partners in campus mental health promotion. Trained peer counselors serve as an accessible first point of contact for fellow students, including those with disabilities who may face academic, emotional, or social barriers. Their presence supports early detection of distress, facilitates timely referrals to professionals, and complements the work of Counselling and Disability Service Unit (Unit Layanan Disabilitas/ULD). Through this initiative, the university’s commitment to inclusive, responsive, and student-centered mental health support is significantly reinforced.